Исследование эффективности нечеткого МГУА с различными видами частных описаний и алгоритмами адаптации в задачах прогнозирования - Зайченко, Ю.П.; Заец, И.О. (Проблемы управления и информатики, 2008)
Розглянуто нечіткий МГУА, який дозволяє будувати нечіткі прогнозуючі моделі в умовах невизначеності. Проведено експериментальні дослідження ефективності запропонованого НМГУА з частинними описами у вигляді квадратичних поліномів, ортогональних поліномів Чебишева, Лагерра та Фур’є. Досліджено ефективність застосування різних методів адаптації прогнозуючих моделей. Проведено порівняльний аналіз з чітким методом МГУА та нейронною мережею Back Propagation. The fuzzy group method of data handling is considered enabling the construction of fuzzy forecasting models under uncertainty. Experimental results of the efficiency of the suggested fuzzy GMDH with partial descriptions in the form of classical quadratic polynomials, orthogonal polynomials of Chebyshev, Lagerr and Fourier are presented. The efficiency of different adaptation algorithms for forecasting models was studied. The comparative analysis of the suggested fuzzy GMDH with classical GMDH and neural network Back Propagation is presented.